PHARMACEUTICAL PREPARATION OF HINGULLOTHA PARADA - R. Hedaoo, *Nalini; B. Bandale, Mukund (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda Classics Rasaushadhi are prepare from Ashtasanskarita Parada because of its Rasayana guna and therapeutic properties, but it require great patience, time, skill and money hence a way has been given in the literature i.e. Hingulatha parada can be used in place of Astha sunskarita parada. Present study done with the aim of pharmaceutical Standardization of Extraction of Hingullotha Parada & study for usefulness of Hingullotha parada instead of Ashtasanskarita Parada in Ayurveda formulations. In the present study Extraction of Hingullotha Parada done three times then last three Sanskaras were done for Gunavardhana. After extraction of Hingullotha Parada % of yield was 42.61 % that is less it may be because of instrumental error. In Ashtasanskara of Parada last three Sanskar Bodhana, Niyamana & Deepan are having Gunavardhana property. Deepan sanskar improve Boobhuksha (bonding capacity) of Parada. After go through the classics it can be conclude that Hingullotha parada can be use instead of Astasanskarit Parada. And last three Sanskara can be doing for Gunavardhana (improving the Rasayana & Rogashamana property of Parada).